2021
DOI: 10.1016/j.eclinm.2021.100763
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant melatonin for the prevention of recurrence and mortality following lung cancer resection (AMPLCaRe): A randomized placebo controlled clinical trial

Abstract: Background: Despite curative intent resection in patients with non-small cell lung cancer (NSCLC), recurrence leading to mortality remains too common. Melatonin has shown promise for the treatment of patients with lung cancer; however, its effect following cancer resection has not been studied. We evaluated if melatonin taken after complete resection reduces lung cancer recurrence and mortality, or impacts quality of life (QOL), symptomatology or immune function. Methods: Participants received melatonin (20 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The use of melatonin in non-small cell lung cancer (NSCLC) patients was also investigated, showing that melatonin improved the quality of life but did not demonstrate any protective effects against chemotherapy-related side effects [ 89 ]. Moreover, adjuvant melatonin following resection of NSCLC increased the 2-year disease-free survival (DFS) in patients with late-stage disease but did not exhibit beneficial effects in quality of life, symptoms, or immune function [ 90 ]. Further studies are needed to explore the beneficial effects of melatonin on this leading cause of death from cancer worldwide.…”
Section: Clinical Trial Based On the Anticancer Effects Of Melatoninmentioning
confidence: 99%
“…The use of melatonin in non-small cell lung cancer (NSCLC) patients was also investigated, showing that melatonin improved the quality of life but did not demonstrate any protective effects against chemotherapy-related side effects [ 89 ]. Moreover, adjuvant melatonin following resection of NSCLC increased the 2-year disease-free survival (DFS) in patients with late-stage disease but did not exhibit beneficial effects in quality of life, symptoms, or immune function [ 90 ]. Further studies are needed to explore the beneficial effects of melatonin on this leading cause of death from cancer worldwide.…”
Section: Clinical Trial Based On the Anticancer Effects Of Melatoninmentioning
confidence: 99%
“…23 Therefore, a total of 19 articles were included in the final meta-analysis. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] The flow chart of the literature search is shown in figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…Melatonin given at a dose of 20 mg at 10 pm has shown particularly positive effects in advanced stages of cancer in earlier studies. 10 It has also been reported that systemic chemotherapy is more easily tolerated in patients who are simultaneously treated with melatonin, particularly in regards to neurotoxicity, thrombocytopenia, weight loss, and asthenia. 44 Furthermore, there are fewer cases of alopecia (hair loss) and infection in patients taking 20 mg of melatonin at 10 pm while undergoing radiotherapy.…”
Section: Follow-upmentioning
confidence: 99%
“…In a recently published study on patients with nonsmall cell lung cancer, a signi cantly improved progression-free survival was seen in a subgroup of patients with advanced stage disease, however, in another, similar study no such impact was seen after a year of treatment with melatonin. 9,10 The overarching factor responsible for melatonin's impact on cancer is believed to be related to its oncostatic properties, including inhibition of tumor cell proliferation, remodeling of the cytoskeleton, antioxidative effects, and stimulation of the immune system. [11][12][13] We have recently described the rationale for adjuvant treatment with melatonin for uveal melanoma in a review of the literature.…”
Section: Introduction Background and Rationalementioning
confidence: 99%